DETERMINAN PERTUMBUHAN EKONOMI SEKTOR PERTANIAN DI KABUPATEN KARANGANYAR - Ita Iva Kuriah; Eni Setyowati (POLITEKNIK LP3I JAKARTA, 2025)
Every region throughout Indonesia plays an important role in driving national economic growth. Local governments, as parties with in-depth understanding of the actual conditions in their regions, are expected to be able to formulate policies that are in line with the needs of the community to support regional economic development. This study aims to analyze the extent of the impact of working capital credit distribution, investment credit, the size of the labor force, and the extent of agricultural land on economic growth, particularly in the agricultural sector in Karanganyar Regency. The research approach used is an empirical approach with quantitative research methods. To meet the data requirements for the research process, the researcher utilized secondary data from Karanganyar Regency for the period 2011–2023. For data analysis, the researcher used multiple linear regression analysis. The results of this study indicate that working capital loans and agricultural land area have a significant impact on economic growth in the agricultural sector in Karanganyar Regency, while investment loans and the labor force do not influence economic growth in the agricultural sector in Karanganyar Regency. The coefficient of determination indicates that the influence of the independent variables, namely working capital loans and the labor force, on the dependent variable, agricultural economic growth in Karanganyar Regency, is 83.1%, while the remaining 16.9% is influenced by other factors outside the variables studied.